2007
DOI: 10.1186/1471-2164-8-475
|View full text |Cite
|
Sign up to set email alerts
|

Surviving extreme polar winters by desiccation: clues from Arctic springtail (Onychiurus arcticus) EST libraries

Abstract: Background: Ice, snow and temperatures of -14°C are conditions which most animals would find difficult, if not impossible, to survive in. However this exactly describes the Arctic winter, and the Arctic springtail Onychiurus arcticus regularly survives these extreme conditions and re-emerges in the spring. It is able to do this by reducing the amount of water in its body to almost zero: a process that is called "protective dehydration". The aim of this project was to generate clones and sequence data in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…The mechanisms by which certain organisms survive extreme low temperatures are schematized in Fig. 10, and they include: extracellular water crystallization (formation of ice crystals outside cell membrane), use of antifreeze proteins (AFPs), and glass formation [235].…”
Section: Survival In Frozen Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms by which certain organisms survive extreme low temperatures are schematized in Fig. 10, and they include: extracellular water crystallization (formation of ice crystals outside cell membrane), use of antifreeze proteins (AFPs), and glass formation [235].…”
Section: Survival In Frozen Environmentsmentioning
confidence: 99%
“…In freeze-tolerant species, proteinaceous ice nucleators agents (INAs) trigger extracellular freezing at high subzero temperatures, either to provide protection from cold by released heat of fusion, or to establish a protective (extracellular) freezing that drives water out of cells, thus decreasing the temperature at which intracellular ice could form [235]. The amino acids within INAs are thought to form templates for ice, which can serve as embryos for ice formation [236].…”
Section: Survival In Frozen Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEA proteins are associated with desiccation tolerance throughout the life cycle of major plant taxa and especially in seeds. They have been found also in non-plant species (nematodes, bdelloid rotifers, Artemia cysts, springtail insects) and almost all non-plant LEA proteins belong to Group 3 (Tunnacliffe & Wise, 2007;Clark et al, 2007), although a Group 1 LEA protein was recently reported in Artemia cysts (Sharon et al, 2009). The exact functions of LEAs are not completely known but they were shown to play a role in protein stabilization, prevent protein aggregation (Chakrabortee et al, 2007) and participate in the intracellular glassy state formation during desiccation in orthodox seeds (Berjak, 2006).…”
Section: Genes Showing Higher Expression Patterns In Resting Eggsmentioning
confidence: 99%
“…15 Most studies on the molecular basis of insect cold hardiness conducted to date have been based on the level of the genome, transcriptome and proteome. [15][16][17][18] Despite significant progress in this area, many aspects of the metabolic adaptations underlying diapause and cold hardiness remain undiscovered, especially in non-model organisms. We propose that a metabolomic approach could provide insight into the metabolite composition underlying adaptations in response to unfavourable environmental conditions, such as low temperature.…”
Section: Introductionmentioning
confidence: 99%